Does capital adequacy ratio matter during the Covid-19 outbreak? Evidence on state-owned banks in Indonesia - Caecilya Putri Diaz; Sari Yuniarti; Eko Aristanto; Yusaq Tomo Ardianto (University of Merdeka Malang, 2022)
The Covid-19 epidemic has led to significant transformations in the financial performance of Indonesia's banking sector. Weak economic indicators have resulted in reduced bank capital due to inadequate working capital loans. This study aims to investigate alterations in the capital adequacy ratio (CAR) of Indonesia's state-owned banks during the Covid-19 pandemic. The dataset is derived from the quarterly financial reports of state-owned banks spanning the period 2020-2021. Our findings establish a relationship between bank lending, non-performing loans (NPLs), and CAR. Under the prevailing circumstances, a considerable decline in credit and a noteworthy upsurge in NPLs emerged starting from the third quarter of 2020, with a slight increase persisting into the third quarter of 2021. In contrast, the capital adequacy ratio exhibits a tendency towards stability, attributed to governmental reinforcement of bank capital. We also prove that bank lending has a positive impact on CAR, whereas NPLs have a negative impact on CAR. The research underscores the state-owned banks' ability to consistently and securely maintain the CAR, further emphasizing that this prudent safeguarding mechanism ensures a continuous capital enhancement in conjunction with lending growth, all the while upholding the regulatory norms of the banking industry.